Beneficial modulation of the gut microbiome by leachates of Penicillium purpurogenum in the presence of clays: A model for the preparation and efficacy of historical Lemnian Earth. - Simon Milling; Umer Zeeshan Ijaz; Danae Venieri; George E Christidis; Nicholas J W Rattray; Iosifina Gounaki; Anna Andrusaite; Aravind Hareendran; Charles W Knapp; Alexander X Jones; Effie Photos-Jones (PLoS ONE)
The experiments presented here are based on the reconfiguration of an ancient medicine, Lemnian Earth (LE) (terra sigillata, stamped earth, sphragis), an acclaimed therapeutic clay with a 2500-year history of use. Based on our hypothesis that LE was not a natural material but an artificially modified one involving a clay-fungus interaction, we present results from experiments involving the co-culture of a common fungus, Penicillium purpurogenum (Pp), with two separate clay slurries, smectite and kaolin, which are the principal constituents of LE. Our results show: (a) the leachate of the Pp+smectite co-culture is antibacterial in vitro, inhibiting the growth of both Gram-positive and Gram-negative bacteria; (b) in vivo, supplementation of regular mouse diet with leachates of Pp+smectite increases intestinal microbial diversity; (c) Pp+kaolin does not produce similar results; (d) untargeted metabolomics and analysis of bacterial functional pathways indicates that the Pp+smectite-induced microbiome amplifies production of short-chain fatty acids (SCFAs) and amino acid biosynthesis, known to modulate intestinal and systemic inflammation. Our results suggest that the combination of increased microbial diversity and SCFA production indicates beneficial effects on the host microbiome, thus lending support to the argument that the therapeutic properties of LE may have been based on the potential for modulating the gut microbiome. Our experiments involving reconfigured LE open the door to future research into small molecule-based sources for promoting gut health.